2023
DOI: 10.3740/mrsk.2023.33.9.360
|View full text |Cite
|
Sign up to set email alerts
|

Partial Substitution of Copper with Nickel for the Superconducting Bismuth Compound and Its Effect on the Physical and Electrical Properties

Kareem Ali Jasim,
Riyam Abd Al-Zahra Fadil,
Kassim Mahdi Wadi
et al.

Abstract: This study focuses on how the partial substitution of copper by nickel nanoparticles affects the electrical and structural properties of the Bi 2 Ba 2 Ca 2 Cu 2.9 Ni 0.1 O 10+δ , Bi 2 Ba 2 Ca 2 Cu 2.8 Ni 0.2 O 10+δ and Bi 2 Ba 2 Ca 2 Cu 2.6 Ni 0.4 O 10+δ compounds. Approximate values of crystallization size and crystallization percentage for the three compounds were calculated using the Scherer, modified Scherer, and Williamson-Hall methods. A great similarity was observed in the crystal size values from the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Studies have shown that the progression is parallel in the cases of low surface roughness, square root, and mean diameter. 24,26) Through the results of the structural characteristics presented, we conclude that the partial replacement of mercury with lead led to a change in all parameters of the crystal lattice through a change in the three lattice axes a, b, and c, which led to a change in the resistivity r, critical temperatures T c(offset) and T c(onset) , as well as the size of the lattice and the proportion of phases. The reason for this is the difference in the sizes of the mercury and lead atoms, while the crystalline structure remains the same, ensuring that all samples have a tetragonal structure.…”
Section: Microscopic Results Of Atomic Forcesmentioning
confidence: 83%
See 1 more Smart Citation
“…Studies have shown that the progression is parallel in the cases of low surface roughness, square root, and mean diameter. 24,26) Through the results of the structural characteristics presented, we conclude that the partial replacement of mercury with lead led to a change in all parameters of the crystal lattice through a change in the three lattice axes a, b, and c, which led to a change in the resistivity r, critical temperatures T c(offset) and T c(onset) , as well as the size of the lattice and the proportion of phases. The reason for this is the difference in the sizes of the mercury and lead atoms, while the crystalline structure remains the same, ensuring that all samples have a tetragonal structure.…”
Section: Microscopic Results Of Atomic Forcesmentioning
confidence: 83%
“…A horizontal crystal evolution takes place when the average diameter increases while the surface roughness, square root, and mean diameter decrease, which lessens crystal defects. 24,25) A vertical crystal evolution takes place when the surface roughness, square root, and mean diameter increase. Studies have shown that the progression is parallel in the cases of low surface roughness, square root, and mean diameter.…”
Section: Microscopic Results Of Atomic Forcesmentioning
confidence: 99%